2006
DOI: 10.1210/me.2005-0185
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Epidermal Growth Factor Network in Ovarian Follicles

Abstract: The LH surge causes major remodeling of the ovarian follicle in preparation for the ovulatory process. These changes include reprogramming of granulosa cells to differentiate into luteal cells, changes in cumulus cell secretory properties, and oocyte maturation. This review summarizes published data in support of the concept that LH stimulation of ovarian follicles involves activation of a local epidermal growth factor (EGF) network. A model describing this property of LH signaling and its branching to other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
218
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(248 citation statements)
references
References 93 publications
(80 reference statements)
13
218
1
5
Order By: Relevance
“…These two effects combine to load the oocyte with cAMP from the CC [39]. In parallel, increases in CC cAMP induce expression of EGF-like peptides and subsequent activation of the EGF receptor and MAPK pathway, thereby stimulating cumulus expansion and oocyte maturation [40][41][42]. It is widely reported that cAMP modulators in cattle IVM extended CC-oocyte GJC and increased oocyte developmental competence [13,19,20,32,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…These two effects combine to load the oocyte with cAMP from the CC [39]. In parallel, increases in CC cAMP induce expression of EGF-like peptides and subsequent activation of the EGF receptor and MAPK pathway, thereby stimulating cumulus expansion and oocyte maturation [40][41][42]. It is widely reported that cAMP modulators in cattle IVM extended CC-oocyte GJC and increased oocyte developmental competence [13,19,20,32,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Sakaguchi et al (2000) observaram aumento da retomada da meiose em COCs bovinos cultivados na presença de EGF, o que não foi presenciado em oó-citos desnudos, sugerindo que o EGF participe do controle da maturação nuclear de forma indireta, via células do cumulus. Desse modo, supõe-se que a expressão do EGFR nas células do cumulus seja requerida para que o EGF desempenhe suas funções (CONTI et al, 2006). Os COCs estão conectados funcional e fisicamente por uma complexa rede de comunicação bidirecional mediada pelas junções gap.…”
Section: Discussionunclassified
“…Esses autores mostraram que COCs obtidos de cadelas nessa fase apresentam as junções gap fechadas. Dessa maneira, Conti et al (2006);Sakaguchi et al (2000) demonstram que a função do EGF na MIV parece sofrer influência das células do cumulus. Essa falta de comunicação existente nos COCs obtidos da fase de anestro poderia explicar, neste estudo, as melhores taxas de metáfase II (p < 0,05) observadas apenas nos oócitos obtidos da fase de diestro, em meios suplementados com EGF.…”
Section: Discussionunclassified
“…Our results bear directly on the mechanisms that are believed to integrate oocyte and cumulus cell physiology and draw attention to the need to optimize IVM for clinical applications. Significant advances in our understanding of the signaling mechanisms deployed during ovulation in rodents have recently been made [13,14,31,35]. The facts that complex signaling cascades are elicited within hours of the LH surge from mural granulosa to cumulus cells, and that reciprocal signals of oocyte origin modulate cumulus expansion serve to re-emphasize the importance of oocyte-granulosa interactions during ovulation.…”
Section: Discussionmentioning
confidence: 99%